Investigations on magnetic bistable PZT-based absorber for concurrent energy harvesting and vibration mitigation: Numerical and analytical approaches. (15th January 2022) - Rezaei, Masoud; Talebitooti, Roohollah; Liao, Wei-Hsin
Abstract: Bistable systems possess broadband characteristics and can have large-amplitude oscillations under low amplitude excitations. This work is aimed to investigate the potential of a bistable piezoelectric-based absorber (BPA) for the purpose of simultaneous energy harvesting and vibration suppression. The BPA composed of a cantilever beam with PZT layers and two permanent magnets. The interactions due to magnets generate bistability in the BPA. Furthermore, the absorber is connected to a main vibrating beam. The governing nonlinear equations are obtained using the Hamilton's principle and a recently developed magnetic force model. Next, numerical analyses in time and frequency domains are performed to characterize the BPA performance in various dynamical regimes. It is found that, the best performance occurs when the BPA exhibits chaotic inter-well oscillations, which lead to strongly modulated response (SMR). Furthermore, approximate-analytical investigations based on the complexification-averaging and multiple scales methods are carried out. Using these, the excitation threshold corresponding to SMR is obtained. The performance of the proposed BPA in terms of harvested power and dissipated energy are examined comprehensively. The results reveal that, the BPA efficiently suppresses the vibration and harvests power over a wide frequency band, and it outperforms a linear absorber and nonlinear energy sink. Highlights: A Bistable PZT absorber for energy harvesting and vibration suppression is investigated. The mathematical model of the coupled magneto-electromechanical system is derived. Time and frequency domain numerical investigations are carried out. Complexification-averaging and multiple scales methods are utilized. Dual-purpose energy harvester efficiency is 127.5% higher than a linear harvester.